2019
DOI: 10.21608/bvmj.2019.17553.1102
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological status of chicken cuts and its products

Abstract: A total of 90 random samples of raw, half cooked (which were exposed to moderate heat treatment) and cooked wings, breast and thigh were collected from supermarkets and restaurant at Qalyubia governorate for evaluation to the microbial status. The obtained results indicated that the mean values of Aerobic plate count for raw samples (wings, breast and thigh) were 4.0×10 6 ±0.3×10 6 , 4.5 ×10 6 ± 0.5×10 6 ,5.7×10 6 ± 0.4×10 6 and for the half cooked were 3.6×10 5 ± 0.2×10 5 , 5.1×10 5 ± 0.2×10 5 ,6.3×10 5 ± 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Referring to the recorded results in table 3, Aspergillus sp. was prominently detected in breast samples other than wings and thighs samples, which came in agree with the previously recorded results of Darwish W, et al (2016) [16] and Shaltout F, et al (2019) [17] who found that the examined breast samples were more contaminated with fungal infection than wing and thigh samples. While the current prevalence of Aspergillus species in the examined samples came lower than those recorded by Hassan W, et al (2019) [18] who found Aspergillus sp.…”
Section: Molecular Detection Of Some Aflatoxin Producing Genes Of Som...supporting
confidence: 91%
“…Referring to the recorded results in table 3, Aspergillus sp. was prominently detected in breast samples other than wings and thighs samples, which came in agree with the previously recorded results of Darwish W, et al (2016) [16] and Shaltout F, et al (2019) [17] who found that the examined breast samples were more contaminated with fungal infection than wing and thigh samples. While the current prevalence of Aspergillus species in the examined samples came lower than those recorded by Hassan W, et al (2019) [18] who found Aspergillus sp.…”
Section: Molecular Detection Of Some Aflatoxin Producing Genes Of Som...supporting
confidence: 91%
“…The uncooked meat can be preserved for more than three to four months by this method. The different types of the meat freezes at different temperature like the meat freezer at -18 o C [65][66][67][68][69][70].…”
Section: The Meat Freezing Methodsmentioning
confidence: 99%
“…Aerobic Plate Count (APC): Determined by the inoculation 0.1 ml of the sample homogenate, at the selected dilutions, onto the duplicate sterile plates of the pre-poured and the dried Standard Method Agar by using the surface spread method, then the plates were incubated for two days at 35°C [41][42][43][44][45][46]. Psychotropic Count: Determined in a similar method to that for APC except that plates were incubated at 7°C for 10 days [47][48][49][50][51][52][53].…”
Section: The Microbiological Analysesmentioning
confidence: 99%